Pseudomonas species prevalence, protein analysis, and antibiotic resistance: an evolving public health challenge - Ayman Elbehiry; Eman Marzouk; Musaad Aldubaib; Ihab Moussa; Adil Abalkhail; Mai Ibrahem; Mohamed Hamada; Wael Sindi; Feras Alzaben; Abdulaziz Mohammad Almuzaini; Abdelazeem M. Algammal; Mohammed Rawway (AMB Express, 2022)
Abstract Psychrotrophic Pseudomonas is one of the significant microbes that lead to putrefaction in chilled meat. One of the biggest problems in the detection of Pseudomonas is that several species are seemingly identical. Currently, antibiotic resistance is one of the most significant challenges facing the world's health and food security. Therefore, this study was designed to apply an accurate technique for eliminating the identification discrepancy of Pseudomonas species and to study their resistance against various antimicrobials. A total of 320 chicken meat specimens were cultivated, and the isolated bacteria’ were phenotypically recognized. Protein analysis was carried out for cultured isolates via Microflex LT. The resistance of Pseudomonas isolates was recorded through Vitek® 2 AST-GN83 cards. Overall, 69 samples were identified as Pseudomonas spp. and included 18 Pseudomonas lundensis (P. lundensis), 16 Pseudomonas fragi (P. fragi), 13 Pseudomonas oryzihabitans (P. oryzihabitans), 10 Pseudomonas stutzeri (P. stutzeri), 5 Pseudomonas fluorescens (P. fluorescens), 4 Pseudomonas putida (P. putida), and 3 Pseudomonas aeruginosa (P. aeruginosa) isolates. Microflex LT identified all Pseudomonas isolates (100%) correctly with a score value ≥ 2.00. PCA positively discriminated the identified isolates into various groups. The antimicrobial resistance levels against Pseudomonas isolates were 81.16% for nitrofurantoin, 71% for ampicillin and ampicillin/sulbactam, 65.22% for cefuroxime and ceftriaxone, 55% for aztreonam, and 49.28% for ciprofloxacin. The susceptibilities were 100% for cefotaxime, 98.55% for ceftazidime, 94.20% for each piperacillin/tazobactam and cefepime, 91.3% for cefazolin. In conclusion, chicken meat was found to be contaminated with different Pseudomonas spp., with high incidence rates of P. lundensis. Microflex LT is a potent tool for distinguishing Pseudomonads at the species level.